Does the public antiretroviral treatment programme meet patients’ needs? A study at four hospitals in eThekwini, KwaZulu-Natal, South Africa - Delarise M. Mulqueeny; Myra Taylor (African Journal of Primary Health Care & Family Medicine, 2019)
Background: Patients play a major role in the success of any antiretroviral treatment (ART) programme. Hence, their needs should be articulated on a regular basis for interventional processes to promote adherence, retention and quality care.